Plant–Insect Interactions: Host Plant Resistance, Biological Control, and Pollination - Francisco Rubén Badenes-Pérez (Plants)
The evolving field of plant–insect interactions impacts basic and applied fields of plant sciences, entomology, and agronomy [...]